2013
DOI: 10.1186/1750-1172-8-125
|View full text |Cite
|
Sign up to set email alerts
|

TBX6, LHX1 and copy number variations in the complex genetics of Müllerian aplasia

Abstract: BackgroundMüllerian aplasia (MA) is a congenital disorder of the female reproductive tract with absence of uterus and vagina with paramount impact on a woman’s life. Despite intense research, no major genes have been found to explain the complex genetic etiology.Methods and ResultsWe have used several genetic methods to study 112 patients with MA. aCGH identified CNVs in 8/50 patients (16%), including 16p11.2 and 17q12 deletions previously associated with MA. Subsequently, another four patients were shown to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
89
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 51 publications
(65 reference statements)
7
89
3
1
Order By: Relevance
“…There are several well-documented cases in the literature, including the 1q21 deletions associated with TAR syndrome (47) or the 16p12 deletions associated with autism (48) and Mullerian aplasia (49). Additionally, it is important to be aware that the aCGH technique does not detect uniparental disomy, a known cause for children being born SGA (14).…”
Section: Discussionmentioning
confidence: 99%
“…There are several well-documented cases in the literature, including the 1q21 deletions associated with TAR syndrome (47) or the 16p12 deletions associated with autism (48) and Mullerian aplasia (49). Additionally, it is important to be aware that the aCGH technique does not detect uniparental disomy, a known cause for children being born SGA (14).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we and other groups found microdeletions and -duplications in patients with müllerian aplasia using array-CGH [Ledig et al, 2011;Nik-Zainal et al, 2011;Sandbacka et al, 2013]. Very recently we could show that patients affected by fusion anomalies of the müllerian ducts are partly carriers of the same microdeletions and -duplications as patients affected by MRKHS [Ledig et al, 2018].…”
mentioning
confidence: 53%
“…Recurrent deletions of this region have previously been reported in both MRKH type 1 and 2 as well as in MURCS [Nik-Zainal et al, 2011] and are reported to contribute to around 1% of MRKH patients [Morcel et al, 2012]. In addition to this, splice site variants of TBX6 , a gene within this region, have been identified in individuals with MRKH [Nik-Zainal et al, 2011;Sandbacka et al, 2013]. Individual MRKH6 also has a VWF variant (c.7390C>T, p.Arg2464Cys), which has previously been reported in a patient with von Willebrand disease with functional validation [Lester et al, 2007].…”
Section: Discussionmentioning
confidence: 82%